Efecto del porcentaje de sacarosa y PH sobre las características reológicas y texturales de almidón de camote (ipomoea batatas l.) variedad morado - Marreros Sánchez, Angela Yanina (2017)
The objective of this research was to determine the effect of sucrose percentage (10, 15 and 20%) and pH (3.4 and 3.5) on the rheological and textural characteristics of sweet potato starch (Ipomoea batatas L.) purple variety. It was determined that the starch gels of the different treatments T1, T2, T3, T4, T5 and T6 exhibited a non-Newtonian flow behavior of the general plastic type following the Herschel Bulkley model. The ANVA showed significant difference between the properties of the treatments (TS) evaluated for values of index of consistency 38.03±1.5 and 41.83±20.29 at pH 4.2; 38.93±5.8 and 47.99±9.15 at pH 5.2 and rheological index of 0.50±0.01 and 0.54±0.06 at pH 4.2; 0.49±0.01 and 0.52±0.01 at pH 5.2. The textural characteristics were determined through the analysis of the texture profile obtained as a result of the difference in hardness values between 430.78±123.67 and 525.12±219.50 at pH 4.2; 409.27±103.32 and 426.39±165.18 at pH 5.2, gumminess of 423.80±118.22 and 522.67±204.16 at pH 4.2; 405.86±101.67 and 418.54±171.01 at pH 5.2, cohesiveness of 0.984±0.01 and 0.997±0.02 at pH 4.2; 0.981±0.02 and 0.992±0.01 at pH 5.2, resilience of 0.424±0.01 and 0.627±0.08 at pH 4.2; 0.602±0.10 and 0.652±0.07 at pH 5.2 for the different levels of sucrose.